Enhancing Reading Comprehension through an Intensive Reading Approach - Andrés Insuasty Cárdenas (HOW)
This article presents a project that explored the effectiveness of intensive reading to enhance reading comprehension with a group of university students in Pasto, Colombia. At the initial stage, a diagnostic test, field notes, and three questionnaires allowed the identification of the students’ needs. During the intervention stage, a set of workshops and reading tests were implemented to reveal the impact of the reading comprehension strategies. In the evaluation stage, four instruments (reading tests, teacher’s journal, students’ questionnaires and pre- and post-tests) were used to collect the students’ opinions and state the results. At the end, findings show that the reading comprehension strategies improved students’ comprehension because it helped them tackle the problems they had before the intervention stage.